Analisis Instrumen dan Prioritas Tindakan untuk Kepuasan Kerja Guru di Indonesia Berdasarkan Pemodelan Rasch - Rais Hidayat; Yuyun Elizabeth Patras; Sutji Harijanto; Lida Hasanah (Universitas Kristen Satya Wacana, 2020)
Teacher job satisfaction is an important variable in achieving educational goals. This research aims to find a research instrument and determine priorities for action in improving teacher job satisfaction in Indonesia. This research instrument was made based on a study of concepts and theories of job satisfaction, interviews with teachers and expert considerations. The instrument is then disseminated via google form to teachers in Indonesia. The number of respondents was 449. The data analyzed by using Rasch modelling. The result of this research are: (1) there are 8 statement items from the teacher job satisfaction instrument which are stated to have validity and reliability with different criteria from conventional validity and reliability tests; (2) there are several significant differences in perceptions on the instrument items so that they can be used to determine priorities for the actions needed to increase teacher job satisfaction in Indonesia. Finally, the results of this study can be used as material for further research